Memetic algorithm based on marriage in honey bees optimization for flexible job shop scheduling problem - Phu-ang, Ajchara; Thammano, Arit (My University, 2017)
This paper proposes a new memetic algorithm based on marriage in honey bees optimization (MBO) algorithm for solving the flexible job shop scheduling problem. The proposed algorithm introduces four new features to the standard MBO algorithm, mainly to get the search to move away from the local optimum: (1) the use of a harmony memory to improve the quality of initial population; (2) the introduction of a new crossover operator called triparental crossover to help increase the genetic diversity in the offspring; (3) the addition of adaptive crossover probability (P c) and mutation probability (P m) to remove the need for users to specify these probabilities; and (4) the incorporation of simulated annealing algorithm embedded with a set of heuristics to enhance the local search capability. The proposed algorithm was evaluated and compared to several state-of-the-art algorithms in the literature. The experimental results on five sets of standard benchmarks show that the proposed algorithm is very effective in solving the flexible job shop scheduling problems.
Keywords: Flexible job shop scheduling problem; Marriage in honey bees optimization; Memetic algorithm; Swarm intelligence